SMART AQUARIUM BASED MICROCONTROLLER - Sembodo, Budi Prijo; Pratama, Novendra Geofanda (BEST, 2021)
Indonesia is an endemic area for the spread of one of the most popular ornamental fish, namely the largest betta fish in the world. In exploring their hobbies such as raising ornamental fish such as betta fish, efficient and automatic tools are more needed by betta fish farmers in aquariums today, when they have no free time or are drained by other work. This study aims to be a more automatic and efficient tool for everyone to feed fish, provide lighting, and drain aquarium water automatically, so that owners of ornamental fish do not have to worry about what ornamental fish need in the aquarium. The feeding system, in this case uses an Arduino-based control that controls the servo motor as an open and close system as the exit of fish feed into the aquarium. Aquarium lighting system, in this system uses a light sensor type LDR (Light Dependent Resistor). Automatic aquarium drain system, controlled by Arduino with water pump output. In the research, the LDR sensor will give a signal to the relay and give output to the 220 V lamp, that is, if the light intensity is below 028.7 Lux, which is above half past 6 pm and will turn off the 220 volt lamp if the light intensity is above 203.4 Lux, which is above 6 am. The servo motor will operate twice a day for feeding according to the betta fish feed needs, which is 2 times a day. The water pump will work every 4 days to drain the water automatically according to the turbidity of the water based on the time and number of betta fish in the aquarium.